Pemanfaatan Artificial Intelligence dan Pelanggaran Rahasia Bank: Studi Kasus Kebocoran Data Nasabah Bank Syariah Indonesia (BSI) ditinjau dari Pasal 40 Undang-Undang Nomor 10 Tahun 1998 tentang Perbankan - Widya Utami; Virda Rachma Mulya; Garnis Putri Shima; Yahya Ayyash; Aditya Rizki Andriyanto; Raden Miko Ardiansyah Judhokusumo (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The rapid digital transformation in the banking sector has significantly changed the management and processing of customer data, particularly within Islamic banking institutions. The use of intelligent computing systems enhances efficiency, transaction speed, and service accuracy, yet it also increases vulnerability to data breaches and violations of bank secrecy. This study examines the leakage of customer data at Bank Syariah Indonesia as a case study, focusing on its legal implications under Article 40 of Law Number 10 of 1998 concerning Banking. Using normative legal research methods, this study analyzes statutory regulations, legal doctrines, and relevant scholarly works to assess the bank’s responsibility for safeguarding customer confidentiality. The findings indicate that data leakage constitutes a violation of bank secrecy obligations and exposes the bank to administrative, civil, and potential criminal liability. Furthermore, inadequate data protection mechanisms weaken customer trust and undermine legal certainty. Strengthening governance frameworks, enhancing digital security systems, and ensuring strict law enforcement are essential to protect customers’ rights and maintain the credibility of Islamic banking in the digital era.